A Critical Threat to Patient Safety: A Bibliometric Analysis of Wrong-site, Wrong-side, and Wrong-organ Surgery - Çankaya, Askeri; Özsoy, Hatice; Gülşen, Muaz; Yavuz van Giersbergen, Meryem (Lippincott Williams and Wilkins, 2025)
Objective: – Wrong-site surgery (WSS) is recognized as one of the most serious yet preventable medical errors in surgical care. It involves operations performed on the wrong anatomic site, side, patient, or at an incorrect level within the correct site. This study aims to systematically investigate prevailing themes, key research areas, and evolving scholarly trends in WSS literature, including wrong-side and wrong-organ surgeries. It also intends to provide a comprehensive resource for stakeholders focused on surgical safety. Methods: – A retrospective descriptive bibliometric analysis was conducted using data retrieved from the Web of Science database on April 9, 2025. A total of 270 articles meeting predefined inclusion criteria were identified. Descriptive and predictive analyses were carried out using Microsoft Excel and ChatGPT. Bibliometric indicators were assessed with the Bibliometrix package in RStudio, while visualizations were generated via VOSviewer. Results: – Between 1980 and 2025, 270 relevant publications were identified, with 28.52% published in the last 5 years, indicating continued academic interest. Spine was the most productive journal. The United States, the United Kingdom, and China were leading in publication output and citation impact. Core keywords such as “wrong-site surgery” and “patient safety” dominated co-occurrence networks. Conclusions: – Despite a modest annual growth rate (1.55%), WSS research remains active. Predictive models indicate a steady increase in publication volume. With an average citation rate of 20.96 per article, the literature reflects meaningful scholarly engagement. This analysis offers critical insight into the intellectual structure and progression of WSS research. © 2025 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: bibliometric analysis; patient safety; wrong level surgery; wrong organ surgery; wrong side surgery